Ordinary eaudiobook - Petosa, Jess (Exceptional, 2015)
"I think your issue is less about localized behavior and more about human nature. I've seen the history books. Someone always has to be better. Someone always has to conquer." Ally and her friends are once again leaving the comfort of home and setting their sights on the Southern City. Does it exist? Will Ally find what she is looking for? Someone will become Exceptional. Someone will die. New friends will be made. Old friends will be lost.